1999
DOI: 10.1017/s095252389916317x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal responses to orientation and motion contrast in cat striate cortex

Abstract: Responses of striate neurons to line textures were investigated in anesthetized and paralyzed adult cats. Light bars centered over the excitatory receptive field (RF) were presented with different texture surrounds composed of many similar bars. In two test series, responses of 169 neurons to textures with orientation contrast (surrounding bars orthogonal to the center bar) or motion contrast (surrounding bars moving opposite to the center bar) were compared to the responses to the corresponding uniform textur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
49
1
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 41 publications
13
49
1
3
Order By: Relevance
“…3b). The reversal of the presentation condition effect with the pop-out, but not with the heterogeneous display condition, is consistent with singlecell physiology studies showing that neural correlates of pop-out can be found as early as in area V1 [22][23][24] . Indeed, such a result is suggestive that V1 may be the source of the signal that modulates the suppressive interactions among multiple stimuli at subsequent stages of processing, consistent with the idea that competitive interactions in extrastriate cortex can be modulated by stimulus context in a bottom-up manner.…”
Section: Experiments 1: Heterogeneous Versus Pop-out Displayssupporting
confidence: 87%
“…3b). The reversal of the presentation condition effect with the pop-out, but not with the heterogeneous display condition, is consistent with singlecell physiology studies showing that neural correlates of pop-out can be found as early as in area V1 [22][23][24] . Indeed, such a result is suggestive that V1 may be the source of the signal that modulates the suppressive interactions among multiple stimuli at subsequent stages of processing, consistent with the idea that competitive interactions in extrastriate cortex can be modulated by stimulus context in a bottom-up manner.…”
Section: Experiments 1: Heterogeneous Versus Pop-out Displayssupporting
confidence: 87%
“…1D). Visual area neurons exhibit stronger responses to a stimulus that differs from neighbor stimuli in some basic visual features than to a stimulus that is identical to surrounding stimuli (e.g., Kastner et al 1999;Knierim and van Essen 1992;Nothdurft et al 1999;Ogawa and Komatsu 2004;Schein and Desimone 1990). Therefore, in the TP trials (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that responses to stimuli in the classical receptive field are modulated by "surround" stimuli outside the receptive filed, and neural responses tend to be stronger when there is feature contrast between the receptive field stimulus and the surround stimuli than when there is no such contrast (Allman et al, 1985;Tanaka et al, 1986;Schein and Desimone, 1990;Knierim and van Essen, 1992;Kastner et al, 1999;Li et al, 2000). The stimulus configuration used in the present study differed from those in earlier studies in that the surround stimuli comprised a relatively small number of independent objects that were separated from the receptive field stimulus by long distances.…”
Section: Neural Modulation By Feature Contrast To Surround Stimulimentioning
confidence: 99%